Outcome of neonates born to mothers with premature rupture of membranes - Ramesh, T. V.; Panigrahi, Bineet; Pranaya, P.; Bindu, P. Hima (International Journal of Contemporary Pediatrics, 2018)
Background: Premature rupture of membranes (PROM) is defined as rupture of membranes before the onset of labor which is caused by maternal intrauterine infection which increases with the duration of membrane rupture seen in one third cases of all preterm birth. The primary complication for the mother is risk of infection, complications for the newborn consists of prematurity, foetal distress, cord compression, deformation and altered pulmonary development. The present study was undertaken to evaluate the outcome of neonates born to mothers with PROM and know the incidence of adverse outcomes in neonates and the incidence of early onset sepsis following PROM more than 18hours in mothers who have not received intrapartum antibiotics. Methods: Prospective cohort study conducted in between December 2015 to November 2017 in which 100 neonates born to mothers with history of Premature rupture of membranes admitted in Konaseema Institute and Medical Science and Research Foundation, Amalapuram were selected for this study. They were evaluated with various investigations by a written proforma and outcomes of these neonates were studied. Results: Out of 100 cases of PROM 54 had 18-24 hours duration, 38 had 24-72hours and 8 had more than 72 hours duration of PROM. According to swab culture organism found were E Coli in 22, Staphylococcus in 20, Klebsiella in 12, Pseudomonas in 8 cases with rest 38 cases showed no growth. 49 out of 100 cases show morbidity with Respiratory distress being the most common with 37 cases followed by septicaemia with 8 cases. Morbidity are more in the neonate with longer duration (>24hrs) of PROM. Mortality increases progressively as the duration of PROM increases. Conclusions: In neonates born after PROM of >24 hours, risk of maternal infection, neonatal morbidity and mortality is more compared to those with PROM of shorter duration. Active management is needed to enable delivery within 24 hrs of premature rupture of membranes as it is associated with better neonatal outcome compared to longer latency period.